Novel wide center-tape balun for 60GHz silicon RF ICs - Meng, Fanyi. (2011)
A novel 60GHz wideband symmetrical balun, named Wide Center-taped Balun (WC-tB) based on Globalfoundries’s 60nm technology node is presented. A technique for achieving excellent output balance with the ultra-wide center-tape is used in designing the balun. The balun uses multilayer coupling between the top two metal layers. The EM-based simulation results reveal excellent performance with a very small loss of -1.3dB and a small phase imbalance around 0.35 degrees over the frequency range from 55 to 66GHz. This performance is the best ever reported and the supported frequency range is sufficient for wideband communication applications at 60GHz. As part of the design process, scalable model is developed for the proposed WC-tB. The modeling approach is fixed corner modeling with scaling range from 40 to 80GHz to cover all possible implementations of WC-tB. This scalable modeling is also technology compatible across different technology nodes.